ORDER OF THE RUNGE-KUTTA METHOD AND EVOLUTION OF THE STABILITY REGION - Hippolyte Séka; Kouassi Richard Assui (Ural Mathematical Journal)
In this article, we demonstrate through specific examples that the evolution of the size of the absolute stability regions of Runge–Kutta methods for ordinary differential equation does not depend on the order of methods.